T BS EN 15119-1. Durability of wood and wood-based products. Determination of emissions from preservative treated wood to the environment. Part 1. Wood held in the storage yard after treatment and wooden commodities exposed in Use Class 3 (not covered, not in contact with the ground). Laboratory method (12th October 2023) - British Standards Institution,
No abstract available